Trigeminal Autonomic Headache Secondary to Submucosal Hemorrhage of Frontal Sinus Caused by Barotrauma - Vasconcelos, Karla Rafaele Silva; Ribeiro, Ian Silva; Landim, João Igor Dantas; Lima, Sylvio Ricard Gonçalves de Souza; Miná, Larissa Brenda Gonçalves; Neri, Pedro Vinicius da Silva; Sampaio, Rhina De Freitas; Carvalho, Pedro Rubens Araújo; França, Mário Hermes Rios; Alcantara, Raimundo Neudson Maia (Headache Medicine, 2023)
Full abstract in PDF.